PENGARUH PERTUMBUHAN EKONOMI DAN JUMLAH PENDUDUK TERHADAP PAJAK DAERAH PROVINSI DI INDONESIA 2009-2012 - Azwardi Azwardi (Jurnal Ekonomi Pembangunan, 2013)
This research was aimed to know the influence of economics growth and population on Indonesian's provinces's regional tax revenue.  The methode of analysis that used in this research is pooling regression. This research used panel data which collected from Statistics Indonesia Finance Ministry from 2009 until 2012 include 33 provinces in Indonesia. The research result showed that the variables economic growth and population had positive influence on Indonesian's provinces regional tax revenue. Keywords : Regional tax, Population and Province's Economic Growth